Global South Asians ; introducing the modern diaspora - Brown, Judith M. (New Delhi, 2007)
By the end of the twentieth century some nine million people of South Asian descent had left India, Bangladesh or Pakistan and settled in different parts of the world, forming a diverse and significant modern diaspora. In the early nineteenth century, many left reluctantly to seek economic opportunities which were lacking at home. This is the story of their often painful experiences in the diaspora, how they constructed new social communities overseas and how they maintained connections with the countries and the families they had left behind. It is a story compellingly told by one of the premier historians of modern South Asia, Judith Brown, whose particular knowledge of the diaspora in Britain and South Africa gives her insight as a commentator. This is a book which will have a broad appeal to general readers as well as to students of South Asian and colonial history, migration studies and sociology. Contents Introduction 1. Traditions of stability and movement 2. Making a modern diaspora 3. Creating new homes and communities 4. Relating to the new homeland 5. Relating to the old homeland Conclusion Bibliography.
Keywords: Social change-South Asia